Geodromicus lestevoides - Shavrin, A. V.; Makarov, K. V. (Zenodo, 2019)
Geodromicus lestevoides (Sharp, 1889) Map 5. Anthophagus lestevoides Sharp, 1889: 470 (type locality: Japan, Hokkaido, Hakodate); Geodromicus lestevoides : Zerche, 2003: 280; Shavrin, 2018: 171. Other references see in Shavrin [2018]. DISTRIBUTION. Russia: Amur Area, Khabarovsk Territory, Maritime Province, Sakhalin Area including Kurile Islands (Kunashir: Map 5). — China (Liaoning), Korea, Japan (Hokkaido, Honshu, Shikoku). BIONOMICS. Detailed ecological data for the specimen collected in Kunashir Island are not available [Shavrin, 2018]. Published as part of Shavrin, A. V. & Makarov, K. V., 2019, Contribution to the knowledge of the fauna of rove beetles of the subfamily Omaliinae MacLeay, 1825 (Coleoptera: Staphylinidae) of Kunashir Island, Kurile Islands, pp. 36-53 in Russian Entomological Journal 28 (1) on page 42, DOI:10.15298/rusentj.28.1.06, http://zenodo.org/record/10978349